1998
DOI: 10.1016/s0006-3495(98)78005-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in Films of Lung Surfactant at the Air-Water Interface

Abstract: Pulmonary surfactant maintains a putative surface-active film at the air-alveolar fluid interface and prevents lung collapse at low volumes. Porcine lung surfactant extracts (LSE) were studied in spread and adsorbed films at 23 +/- 1 degrees C using epifluorescence microscopy combined with surface balance techniques. By incorporating small amounts of fluorescent probe 1-palmitoyl-2-nitrobenzoxadiazole dodecanoyl phosphatidylcholine (NBD-PC) in LSE films the expanded (fluid) to condensed (gel-like) phase transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
168
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(185 citation statements)
references
References 57 publications
15
168
1
1
Order By: Relevance
“…It is not yet known whether POPG can exist in segregated domains within the surfactant monolayer or within the alveolar hypophase present in the lung. However, biophysical studies provide good evidence that DPPC can exist in distinct domains in the surfactant layer, and thus, it is plausible that POPG could also be present in segregated domains (48). In our studies, the highest levels of POPG or PI used are only 10% of the levels found in the alveolar compartment of the lung.…”
Section: Phospholipid Antagonism Of Lps-induced Inflammationmentioning
confidence: 48%
“…It is not yet known whether POPG can exist in segregated domains within the surfactant monolayer or within the alveolar hypophase present in the lung. However, biophysical studies provide good evidence that DPPC can exist in distinct domains in the surfactant layer, and thus, it is plausible that POPG could also be present in segregated domains (48). In our studies, the highest levels of POPG or PI used are only 10% of the levels found in the alveolar compartment of the lung.…”
Section: Phospholipid Antagonism Of Lps-induced Inflammationmentioning
confidence: 48%
“…It is recognized that spread and adsorbed films containing gel phase phospholipids can spontaneously form liquid condensed domains enriched in DPPC (54,(62)(63)(64) [as reviewed in ref. (19)].…”
Section: Discussionmentioning
confidence: 99%
“…However, cholesterol is well recognized as a component that provides mechanical stability to cell membranes [48] and an important structural element to modulate their lateral structure, including segregation of specialized domains such as lipid rafts [49,50]. Recent results have shown that physiological proportions of cholesterol modulate the lateral organization and distribution of proteins and lipids in pulmonary surfactant membranes [51] and films [52,53], as well as the dynamical behaviour of surfactant films subjected to compression-expansion cycling [54]. Presence of cholesterol could be particularly important to permit surfactant films to reach and sustain the lowest surface tensions at 100% humidity [55], a condition thought to exist in the alveolar spaces but poorly reproduced in in vitro models.…”
mentioning
confidence: 99%